2019
DOI: 10.1002/ppp3.10076
|View full text |Cite
|
Sign up to set email alerts
|

Buying better biosecurity: Plant‐buying behaviour and the implications for an accreditation scheme in the horticultural sector

Abstract: The horticultural trade relies on healthy plants to flourish. However, its very nature means that it is also a key pathway for the introduction and spread of plant pests and diseases. These pests and diseases threaten horticultural stakeholders, and can also cause huge ecological and economic damage. A horticultural sector accreditation scheme, underpinned by best biosecurity practice, could help reduce these threats. Drawing on survey responses, this study examines the plant-buying habits of UK consumers and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…A previous study into the general publics' tree and plant purchasing decisions demonstrated the importance of perceptions of quality and cost over biosecurity precautions and the associated mitigation of damage to the wider environment from pests and diseases, for which awareness is low. Although many supported the notion of an accreditation scheme underpinned by best-biosecurity practice they also expressed concern over whether a nursery's requirement to implement practices and join a scheme would impact the affordability of products [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study into the general publics' tree and plant purchasing decisions demonstrated the importance of perceptions of quality and cost over biosecurity precautions and the associated mitigation of damage to the wider environment from pests and diseases, for which awareness is low. Although many supported the notion of an accreditation scheme underpinned by best-biosecurity practice they also expressed concern over whether a nursery's requirement to implement practices and join a scheme would impact the affordability of products [29].…”
Section: Discussionmentioning
confidence: 99%
“…We recently explored whether the gardening public would be receptive to a biosecurity accreditation scheme in the nursery sector and there was wholescale support in principle although less willingness to pay more for accredited products [29]. Here, we will identify where there is support for an accreditation scheme within the nursery sector that grow, purchase and trade large volumes of plants.…”
Section: Introductionmentioning
confidence: 99%
“…The role of this panel was to help steer the project's science outcomes to match stakeholder needs. A wide range of stakeholder and consumer attitudes to implementation of a UK-wide nursery 'best practice' accreditation scheme was identified through surveys and interviews [26,27]. These analyses involved growers, retailers, local authorities, landscape architects and the general public.…”
Section: Is Nursery Accreditation In the Uk Feasible And If So What Should It Look Like?mentioning
confidence: 99%
“…Research carried out by social scientists in the Phyto-threats project explored attitudes towards a hypothetical accreditation scheme. A survey of 100 UK garden centres and nurseries [26] identified strong agreement within these sectors that an accreditation scheme would provide greater biosecurity protection and ensure that consumers purchased better quality plants. However, there were concerns over costs and a degree of scepticism over the likely interest of consumers in accredited products.…”
Section: Stakeholder Workhops Enabled Tracking Of Wider Attitudes Towards Accreditationmentioning
confidence: 99%
See 1 more Smart Citation